2017
DOI: 10.3390/s17051023
|View full text |Cite
|
Sign up to set email alerts
|

A New Electromagnetic Acoustic Transducer Design for Generating and Receiving S0 Lamb Waves in Ferromagnetic Steel Plate

Abstract: Electromagnetic acoustic transducers (EMATs) are non-contact, ultrasonic transducers that are usually kept within 5 mm from the sample surface to obtain a sufficient signal-to-noise ratio (SNR). One important issue associated with operation on a ferromagnetic plate is that the strong attraction force from the magnet can affect measurements and make scanning difficult. This paper investigates a method to generate fundamental, symmetric Lamb waves on a ferromagnetic plate. A coil-only, low-weight, generation EMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…A configuration of a coil with a bias magnetic field is usually applied in conventional EMATs, whose mechanisms mainly include Lorentz force and magnetostriction (for magnetic materials). Previous work shows that magnetostriction becomes the main contributor and the Lorentz force could be ignored when the lift-off of a coil-only transducer is more than 7 mm [26]. The coil-only transducer is employed as the excitation transducer in these experiments with a 10 mm lift-off.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A configuration of a coil with a bias magnetic field is usually applied in conventional EMATs, whose mechanisms mainly include Lorentz force and magnetostriction (for magnetic materials). Previous work shows that magnetostriction becomes the main contributor and the Lorentz force could be ignored when the lift-off of a coil-only transducer is more than 7 mm [26]. The coil-only transducer is employed as the excitation transducer in these experiments with a 10 mm lift-off.…”
Section: Methodsmentioning
confidence: 99%
“…10. Lamb waves are usually generated in the plate sample, and the simulated S0 Lamb wave is the first wave to reach the detection point, followed by the A0 Lamb wave [26], as shown in the Fig. 10.…”
Section: Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the phase velocity and amplitude changes of Lamb waves obtained by simulation were in good agreement with experiment. He et al [31] designed two electromagnetic acoustic transducers to generate and receive S 0 Lamb waves in ferromagnetic steel plates, which were kept within 5 and 19 mm from the sample surface, respectively. This allowed the electromagnetic acoustic transducer to interact with the sample with less force and facilitated easier scanning.…”
Section: Transducers For Lamb Wavesmentioning
confidence: 99%